Variability of cadmium accumulation in cephalopods (Octopus vulgaris, Sepia officinalis, Loligo vulgaris and Todarodes sagittatus) collected in Sardinia in 2008-2012 - Pierluigi Piras; Giannina Chessa; Maurizio Cossu; Federica Rubattu; Gianuario Fiori (Italian Journal of Food Safety, 2013)
Cephalopods are known to accumulate cadmium and play an important role in its biomagnification. They are an essential link in marine trophic chain and represent an important case in studies on cadmium transfer to man through the food chain. Since cadmium concentration widely varies in different tissues of the cephalopods – mainly accumulating in the hepatopancreas – evisceration represents a recommended preliminary step to reduce cadmium intake in view of cephalopods consumption; yet, the residual concentration in the edible part may still be a risk for public health. This study is intended to assess cadmium levels variability in the muscles of Cephalopoda, considering the different feeding habitats and marine trophic webs. In compliance with EU regulation, a survey on cadmium and other heavy metal levels in various sea food, including cephalopods, was conducted by the Istituto Zooprofilattico of Sardinia in co-operation with local health authorities. During a five-year survey (2008- 2012), 90 samples were collected from the following species: commons octopus (Octopus vulgaris), cuttlefish (Sepia officinalis), European squid (Loligo vulgaris), and flying squid (Todarodes sagittatus), located in different coastal areas and representatives of either benthic or nektonic habitats. Determination of cadmium levels was carried out according to Regulations (EC) No. 882/2004, No. 1881/2006 and No. 333/2007. Analysis of the edible portion (muscle) of fresh homogenised samples was carried out by inductively coupled plasma mass spectrometry (ICP-MS). The results showed a highly skewed distribution of data. No statistically significant differences were observed among four distributions of the natural logs of cadmium levels in the species considered.